Klasyfikacja rezerw w rachunkowości jednostkowej - przegląd literatury przedmiotu - Orzeszko, Teresa (Classification of Reserves in Unit Accountancy - the Review of Polish Literature on the Subject, 2006)
There exists, beyond any doubt, the need of reserves' classification in unit accountancy, since it is determined by their diversity. Everybody also agrees that it should enable the understanding the complex nature of reserves and their scope, which could be perceived from different angles. Differences in views occur with regard to the ways of conducting such classification, as a result of which in the literature on the subject one can encounter different proposals in this matter. Their analysis and conclusions resulting from it lead towards the final conclusion, which Is as follows: so far we have not been successful in our country to create one, generally accepted classification of reserves for the needs of unit accountancy, there is also no consensus with regard to the number and kinds of desirable criteria, as well as with reference to the nomenclature of the criteria themselves, distinguished on their basis. The study of literature does not facilitate the straightforward answer to the question: how the reserves should be classified in unit accountancy. The reason of this state of affairs is, among others, the diversified perception of reserves in this discipline and different ways of defining them. Creating versatile, coherent and precise, as well as transparent classification of reserves would undoubtedly facilitate understanding of their nature and scope and their clear analysis, both for the needs of accountancy theory and practice. Going even further it would enable generating, by means of accountancy, more reliable and clear information regarding the assets and financial situation of entities running it, which is undoubtedly its purpose.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 107-122